English English: Bahasa Indonesia - Ayustyawati .; Warih Handayaningrum (Jurnal Pendidikan Sendratasik, 2025)
Local dance can function not only as a form of cultural expression but also as a pedagogical medium for character formation. Nevertheless, empirical studies examining how locally created choreography represents and transmits educational values within formal arts education remain limited. This study examines the educational values embedded in Sayuk Dance, created by Renny Nurwitadiarti, and analyzes its integration into Arts and Culture learning at an Indonesian junior high school. A qualitative descriptive design was employed, with data collected through classroom observations, semi-structured interviews with the choreographer who also served as the Arts and Culture teacher and seventh-grade students, and analysis of instructional and performance documentation. The data were analyzed through data reduction, data display, and conclusion drawing. Research credibility was established through source, technique, and time triangulation. The findings identified five interrelated educational values: tolerance, mutual cooperation, discipline, teamwork, and environmental care. These values were represented through synchronized group movements, floor patterns, costumes, musical accompaniment, and the symbolic use of bamboo-basket waste bins and coconut-leaf brooms. Sayuk Dance was integrated into learning through dance appreciation, simplified movement practice, collaborative rehearsals, reflection, and performance within the Pancasila Student Profile Strengthening Project focusing on local wisdom. Observational and interview evidence indicated that participation in these activities strengthened students’ cooperation, responsibility, discipline, environmental awareness, and respect for differences. The findings demonstrate that locally created choreography can provide contextual learning material that connects artistic competence with character education and environmental values. This study further highlights the pedagogical role of school-based dance creation in maintaining local cultural knowledge and supporting culturally grounded arts education.